Willingness to Communicate (WTC) in English: Insights from Pre-service EFL Teachers - Mudra, Heri (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
Oral language skill among EFL students can be indicated from willingness to communicate in English. This current study aimed to investigate pre-service EFL teachers’ (PST) willingness to communicate (WTC) in English across rural setting. A survey study with 217 EFL students as the participants selected through a convenience sampling was employed. A questionnaire of the willingness was distributed through in-class meeting and online mode. The first result revealed that there is a variety of perceptions on oral skill willingness, self-confidence, and English use frequency. The second result showed that from junior and senior PST, it is noted that seniors mostly overdid juniors in terms of willingness to speak English. Meanwhile, female PST had greater levels of WTC if compared to that of the males. In conclusion, WTC not only emerge to be a valuable aspect in learning oral language skills, but also impact on other English skills indirectly.